Increases in mitochondrial biogenesis impair carcinogenesis at multiple levels - Xiao Wang; Carlos T. Moraes (Molecular Oncology)
Abstract Although mitochondrial respiration is decreased in most cancer cells, the role of this decrease in carcinogenesis and cancer progression is still unclear. To better understand this phenomenon, instead of further inhibiting mitochondrial function, we induced mitochondrial biogenesis in transformed cells by activating the peroxisome proliferator‐activated receptors (PPARs)/peroxisome proliferator‐activated receptor gamma co‐activator 1α (PGC‐1α) pathways. This was achieved by treating the cells with bezafibrate, a PPARs panagonist that also enhances PGC‐1α expression. We confirmed that bezafibrate treatment led to increased mitochondrial proteins and enzyme functions. We found that cells with increased mitochondrial biogenesis had decreased growth rates in glucose‐containing medium. In addition, they became less invasive, which was directly linked to the reduced lactate levels. Surprisingly, even though bezafibrate‐treated cells had higher levels of mitochondrial markers, total respiration was not significantly altered. However, respiratory coupling, and ATP levels were. Our data show that by increasing the efficiency of the mitochondrial oxidative phosphorylation system, cancer progression is hampered by decreases in cell proliferation and invasiveness.